2005
DOI: 10.1007/s11274-005-7371-6
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Digestion of Dairy Manure in a Hybrid Reactor with Biogas Recirculation

Abstract: A novel anaerobic hybrid reactor (AHR) configuration incorporating floating support media for biomass immobilization and biogas recirculation for enhanced mixing was used for anaerobic digestion of dairy manure. No pretreatment or solid liquid separation was applied. The reactor was operated at high influent volatile solids (VS) and organic loading rates (OLR) of up to 9.87% and 7.30 g VS/l day, respectively. After 149 days of continuous operation the results revealed that a high amount (38.1 g VSS) of biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 37 publications
6
21
1
1
Order By: Relevance
“…The negative value of ammonia nitrogen removal in Table 1 corresponds to an increase in the reactor. This is an observation also reported by other researchers [20][21][22]. The alkalinity was reduced by 15.8 (±8.8)% on average.…”
Section: Phasesupporting
confidence: 90%
See 1 more Smart Citation
“…The negative value of ammonia nitrogen removal in Table 1 corresponds to an increase in the reactor. This is an observation also reported by other researchers [20][21][22]. The alkalinity was reduced by 15.8 (±8.8)% on average.…”
Section: Phasesupporting
confidence: 90%
“…The removals in TP and also the loss of N in the UASB should be due to both new biomass production, as well as settling in the reactor [19]. Relatively low treatment efficiencies may be expected for TKN and TP, since anaerobic reactors are known to reduce negligible amounts of nutrients [20]. The NH 3 -N concentration on average was increased by about 21 (±11.8)% during Phase 1 because of the anaerobic bioconversion of proteins contained in manure into amino acids and then to ammonia [20].…”
Section: Phasementioning
confidence: 99%
“…d and HRT not exceeding 6.0 h. An increase in the HRT would result in a decrease in the wastewater linear velocity through the support material, improving the mass transfer from the liquid phase to the biomass and, therefore, favoring the process performance (Elmitwalli et al, 2000). The removal efficiency of CODtotal in an AH reactor at an HRT of 4.3 h was higher than those obtained by Demirer and Chen, (2005) who used AH reactor for treatment of dairy wastewater at longer HRT of 15 days.Also, Gu¨ngo¨r and Demirer, (2004) achieved a lower COD removal efficiency of 37.9-50% in anaerobic batch reactor treating food industry wastewater.. The improved removal efficiency of CODtotal in this study was mainly due to a higher removal efficiency of COD particulate as shown in Fig.…”
Section: Efficiency Of Ah Reactor As a Pretreatment Of Tomato Wastewacontrasting
confidence: 66%
“…It has to be underlined at this point that a 35% reduction in the AD performance is neither suggested nor acceptable. However, it can be considered as a loss which can be recovered by pretreatment (Hartmann et al, 2000;Schieder et al, 2000;Angelidaki and Ahring, 2000), phase separation Chen, 2004, 2005a), or enhanced process configuration (Demirer and Chen, 2005b). So it is still noteworthy to investigate the reactors with less than 35% reduction in GP, since their NH 3 removals were superior to that of the control reactor.…”
Section: Article In Pressmentioning
confidence: 99%